PELAKSANAAN PEMBAYARAN ROYALTI ATAS LAGU DALAM LIVE PERFORMANCE KEPADA PENCIPTA LAGU DI KAFE ROEMAH KESAMBI KOTA CIREBON - Kharisma, Fahmi (JIPRO: Journal of Intellectual Property, 2022)
This research aims to examine the implementation of royalty payments for songs in live performance to songwriters at the Kopi Roemah Kesambi cafe, Cirebon City, towards Law Number 28 of 2014 concerning Copyright and Government Regulation Number 56 of 2021 concerning Management of Royalties Copyright Song or Music and legal effort that the author may take against songs performed in musical performances without permission. This research belongs to the type of empirical research where the authors obtain research data from direct interviews with the Coffee Roemah Kesambi cafe, Cirebon City. The analysis in the study was carried out by qualitative analysis. The results of the research explain that the live music held at the Roemah Kesambi Coffee Cafe, Cirebon City has taken permission of a license permit before the live music is carried out, and the calculation of royalties that must be paid by the cafe to LMK is done by taking 3% of sales revenue on the day the live music is held. The legal effort that can be taken by the creator if there is a violation of using songs in live music without permission, namely, Alternative Dispute Resolution (ADR), Civil Lawsuits as regulated in Article 97 paragraph (1) of Law Number 28 of 2014, and Criminal charges are regulated in Article 113 paragraph (1), paragraph (2) and paragraph (3) of Law Number 28 of 2014.